2020
DOI: 10.30552/ejhr.v6i1.201
|View full text |Cite
|
Sign up to set email alerts
|

Role of the exercise of high intensity intervals (HIIT) in health in the older adults: A systematic review of randomized clinical trials

Abstract: Despite growing interest in high-intensity interval training as a time-effective way for older adults to improve their health, there is little consensus regarding the better way to plan a HIIT intervention. Given the loss of function and health problems of an older adult population, the identification and characterization of interventions and strategies is a fundamental prerequisite. The goals of this review are examining high-intensity interval training as a way to improve health, and finding out the highesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Yet, previous studies have shown that the cycle ergometer was the most common type of HIIT instrument used among older persons, followed by treadmill walking [59]. Furthermore, previous reviews recommended cycling (cycle ergometer) as an effective HIIT modality to improve cardiometabolic and cardiovascular health in older persons, including additional benefits in terms of accessibility, safety, and decreased stress on joints [59][60][61].…”
Section: Modalitymentioning
confidence: 99%
“…Yet, previous studies have shown that the cycle ergometer was the most common type of HIIT instrument used among older persons, followed by treadmill walking [59]. Furthermore, previous reviews recommended cycling (cycle ergometer) as an effective HIIT modality to improve cardiometabolic and cardiovascular health in older persons, including additional benefits in terms of accessibility, safety, and decreased stress on joints [59][60][61].…”
Section: Modalitymentioning
confidence: 99%